FINANCIAL LITERACY AND THE SUSTAINABLE LIVELIHOOD FRAMEWORK: ADVANCING ECONOMIC INDEPENDENCE AND FOOD SECURITY - Rudi Kurniawan; Amru Alba; Safrida; Fidhia Aruni; Cut Annisa Fitriati; Nodi Marefanda (Universitas Negeri Yogyakarta, 2025)
The dependence of PKH and low financial literacy have led to weak economic independence and food security among low-income families. This study aims to develop a Sustainable Livelihood Frameework (SLF)-based financial literacy model to improve household financial management, encourage productive behavior, and enhance sustainable household food security. The research method used a qualitative approach through in-depth interviews, which were then analyzed through NVivo thematic coding. The research results show a duality: some families have succeeded in escaping poverty, while others remain dependent on the PKH. This is based on findings in the SLF Analysis related to financial literacy, which shows that PKH recipients still face context, conditions, and trends of inflation and social stigma. Meanwhile, livelihood resources are still weak and are utilized in a limited manner. Institutional processes and organizational structures are still not optimal in terms of multisectoral coordination. However, in terms of livelihood strategies, recipients are divided into groups with passive consumption patterns and active diversification through small businesses or agriculture. These conditions present highly varied livelihood outcomes, with some experiencing economic recovery, improved welfare, and human resource quality, while others are trapped in financial dependence and consumptive lifestyles. This study confirms that PKH policy formulation needs to prioritize sustainability, which can be achieved through the integration of financial literacy, consistent institutional support, and cross-sector collaboration.